2022
DOI: 10.1371/journal.pone.0278097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of wasting of under-5 children in Bangladesh: Quantile regression approach

Abstract: Background Wasting is perhaps one of the signs of malnutrition that has been linked to the deaths of children suffering from malnutrition. As a result, understanding its correlations and drivers is critical. Using quantile regression analysis, this research aims to contribute to the discussion on under-5 malnutrition by analyzing the predictors of wasting in Bangladesh. Methods and materials The dataset was extracted from the 2017–18 Bangladesh demographic and health survey (BDHS) data. The weight-for-height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…The demand for nutritious food increases with the age of the child but underdeveloped and developing countries are not fully capable to meet the demand for nutritious food which leads to child malnutrition. A previous study in Bangladesh has also corroborated similar relationship (Rahman et al, 2016); however, researchers pointed out that the status of stunting and wasting decreased as the child's age increased (Abdulla et al, 2023;Hossain et al, 2022). While this study shows a significant association between birth order and nutritional status, it does show a negligible difference in nutritional status due to changes in birth order.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The demand for nutritious food increases with the age of the child but underdeveloped and developing countries are not fully capable to meet the demand for nutritious food which leads to child malnutrition. A previous study in Bangladesh has also corroborated similar relationship (Rahman et al, 2016); however, researchers pointed out that the status of stunting and wasting decreased as the child's age increased (Abdulla et al, 2023;Hossain et al, 2022). While this study shows a significant association between birth order and nutritional status, it does show a negligible difference in nutritional status due to changes in birth order.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies highlighted that the height of the mother, household food insecurity, residence, region, age of the mother, and socioeconomic status of a family had a significant effect on malnutritional status (Félix‐Beltrán et al, 2021; Rahman & Hossain, 2022). Previous studies conducted on demographic and health survey data have revealed that several sociodemographic and socioeconomic factors are the influential determinants of child malnutrition (Abdulla, El‐Raouf, et al, 2022; Hossain et al, 2023; Hossain et al, 2021; Panda et al, 2020; Perez‐Escamilla et al, 2018; Rahman et al, 2021; Rahman et al, 2020; Sazedur et al, 2020). The growth in overweight and obesity in Bangladesh is a result of the country's population shifting from a traditional diet of rice, vegetables, and lentils to one that is more Westernized and includes processed foods, sugary beverages, and snacks (Popkin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The quantile regression (QR) model was initially introduced by Koenker and Basset in 1978, and nowadays it is extensively applied in various research areas, particularly statistics, econometrics, and public health [ 55 , 60 65 , 67 69 ]. Suppose Y is a random (response) variable having cumulative distribution function (CDF) F Y ( y ), i.e., F Y ( y ) = P ( Y ≤ y ) and X is the p-dimensional vector of predictor variables.…”
Section: Methodsmentioning
confidence: 99%
“…Borooah (2005) applied the QR model to capture the heterogeneity and the determinants of height-for-age in India [ 60 ]. Many more studies have also used the QR model for similar purposes [ 55 , 61 65 ]. Therefore, it was crucial to estimate the robust measure of the heterogeneous effect of the significant risk factors of child stunting for designing an effective intervention package to lessen the prevalence of stunting among children in the context of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…However, particularly in Bangladesh, poverty, insufficient treatment, gender biases in decision-making, inadequate breastfeeding and complementary feeding rates, insufficient sanitation, environmental variables and recurring illnesses are only a few of the numerous factors of stunting that have been thoroughly investigated (11,18,20,22,28,29) . Also, many studies consider factors including the age of parents and child, health condition of both parents, birth spacing, paternal and maternal education, and access to media for determining childhood malnutrition (7,12,13,17,20,28,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) . Moreover, the study of malnutrition is exceptionally crucial for a South Asian developing country like Bangladesh, as it is a member of the world's most stunted countries (under-fiveyear-old children account for 36 % of stunted children, and 12 % of these children are severely stunted) and is attempting to achieve the Sustainable Development Goals (12 of the 17 sustainable development goal contain nutritional indicators, particularly in goal 2).…”
mentioning
confidence: 99%